2016
DOI: 10.1002/cam4.891
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin suppresses lung cancer growth by targeting Aurora B kinase

Abstract: Abstractaurora B kinase is highly expressed in several cancer cells and promotes tumorigenesis and progression, and therefore, it is an important target for drug to treat tumors. Quercetin was identified to be an antitumor agent. Herein, we report for the first time that quercetin inhibited aurora B activities by directly binding with aurora B in vitro and in vivo. Ex vivo studies showed that quercetin inhibited aurora B activities in JB6 Cl41 cells and A549 lung cancer cells. Moreover, knockdown of aurora B i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…For JB6 Cl41 cells and A549 lung cancer cells, researchers showed that quercetin inhibits aurora B activities and reduces the phosphorylation of histone 3 (Xingyu et al, ). Quercetin also reduces ROS production induced by exposure to hexavalent chromium [Cr(VI)] in BEAS‐2B cells.…”
Section: Anticancer Perspectives Of Quercetinmentioning
confidence: 99%
“…For JB6 Cl41 cells and A549 lung cancer cells, researchers showed that quercetin inhibits aurora B activities and reduces the phosphorylation of histone 3 (Xingyu et al, ). Quercetin also reduces ROS production induced by exposure to hexavalent chromium [Cr(VI)] in BEAS‐2B cells.…”
Section: Anticancer Perspectives Of Quercetinmentioning
confidence: 99%
“…QR exhibits anticancer activity in lung cancer (A549 cells) by activation of the MEK–ERK pathway along with inactivation of Akt-1 and variation in expression of Bcl-2 family (proteins) 42. QR suppresses the growth of a variety of NSCLC cell lines by inhibiting overexpressed Aurora-B kinase and can be used for lung cancer therapy 43. However, the application of QR in lung cancer therapy has been restricted by a number of factors, ie, low water solubility (2.15 µg/mL), low bioavailability and rapid clearance from plasma 44,45.…”
Section: Introductionmentioning
confidence: 99%
“…In general, when used alone, pure phenolic compounds have been effective in decreasing cell viability or activating cell death at micromolar concentrations. This has been shown, for example, for apigenin and curcumin in SH-SY5Y neuroblastoma cells [1,18,19] or naringenin and quercetin in A549 small lung cancer cells [20,21]. Therefore, we propose that the effects of JE were due to the potentiation, synergy, or both between several plant polyphenols through common or different mechanisms.…”
Section: Discussionmentioning
confidence: 64%